The creation of a risk-based insurance policy for the print collection of the UP Main Library based on the risks of fire damage and factors leading to rebinding and replacement - Ramirez, Jess Christian D.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
The UP Main Library serves as the "heart" of the University. Consisting of three majors divisions: Technical Service, Administrative Service and User Education and Services Division, the UPML performs the task of being the primary information resource of the students, faculty, staff and the community of UP Diliman.
As part of disaster and risks preparedness, the research investigated on the different types of risks associate with the print collection of the UPML. Also the research analyzed the changes in the budget, or in case, the Book Fund of the UPML, by factoring in the effects of inflation. By using the CPI, the real values of the Book Fund have been plotted against time and net increase and decrease in the budget were observed.
The three major types of risks assessed are the following: fire damage, factors that lead to binding and lastly factors that lead to the replacement of materials. The number of holdings or materials maintained by the library section were given value and the probability of library fires was computed.
The cost of factors leading to binding were computed by tabulating the total number of requests for binding. This include the number of volumes sent to the Bindery (in-house or commercial) and the total cost of the service. Last is the risk of factors leading to replacement of library print materials. This include but are not limited to loss, theft, infestation and unaccounted print materials. The cost of materials under these risks were given value using the same computation for giving values for the cost of holdings as seen in the earlier risk which is fire damage.
The final value of premium was computed and the following are the cost per each type of risk: Fire Damage (P4,156,026 or 89.89% of the premium), Causes of Binding/Rebinding (P384,931 or 8.33% of the premium). And lastly, Cause of Replacement (P82,511 or 1.78% of the premium).
The Institution can then decide on the period in which it is going to pay for the premium and thus the divisor will depend on the number of years the premium will be paid. The final request for the budget may come from the predicted budget plus the amount of premium to be paid for that particular year.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library; Emergency management -- Philippines -- Quezon City; Libraries -- Philippines -- Insurance